Two new species of the sponge associated axiid shrimp genus Eiconaxius Bate, 1888 (Decapoda: Axiidea) from seamounts in the Nishi-Shichito Ridge, Japan - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2024)
Two new species of the axiid shrimp genus Eiconaxius Bate, 1888, are described from seamounts in the Nishi-Shichito Ridge, northwestern Pacific off Japan, during recent cruises of R/V Kaimei of the Japan Agency for Marine-Earth Science and Technology, exploring the marine protected area (MPA). Eiconaxius latirostrum sp. nov. is described on the basis of three specimens from Shoho Seamount at depths of 402–456 m; and E. kaimei sp. nov. is described on the basis of a single ovigerous female from An’ei Seamount at a depth of 888 m. The status of the two new taxa was assessed by phylogenetic analyses employing two mitochondrial markers (16S rRNA and COI genes) and morphological comparison. Specimens of the two new species lived in colonies of unidentified farreid sponges. This study contributes to documenting the benthic invertebrate fauna of the Japanese MPA as a baseline data for conservation.